Separations at the Firm Level - Pieter A. Gautier; Gerard J. van den Berg; Jan C. van Ours; Geert Ridder (Tinbergen Institute, 1999)
This paper analyzes the determinants of lay-offs, job-to-job movements and totalseparations with a unique data set that combines information on individual firmsand their workers. We are in particular interested in whether the lay-offpolicy of firms can explain the relatively high level of unemployment amongstlower educated workers and the relatively strong sensitivity of their unemploymentrate to the business cycle. We find that lay-off rates decrease with educationbut that the change over the cycle in the lay-off rate of workers with a lowerlevel of education compared to that of workers with a higher level of education can notexplain the stronger cyclicality of the unemployment rate for lower educatedworkers. We conclude that this stronger cyclicality is not due to the personnelpolicy of firms.
Keywords: 330; Arbeitslosigkeit; Arbeitsmobilität; Kündigung; Niederlande